2016
DOI: 10.1002/rra.3066
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Prescribed Flows for Salmon Smolt Survival Enhancement Vary Longitudinally in a Highly Managed River System

Abstract: The influence of streamflow on survival of emigrating juvenile Pacific salmonids Oncorhynchus spp. (smolts) is a major concern for water managers throughout the northeast Pacific Rim. However, few studies have quantified flow effects on smolt survival, and available information does not indicate a consistent flow-survival relationship within the typical range of flows under management control. In the Yakima Basin, Washington, the potential effects of streamflow alterations on smolt survival have been debated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Moreover, we observed that higher flow at the reach scale had a more positive effect on survival in dry years with low flow than it did in wet years with high flow. Although the interaction between annual flow and intra‐annual reach flow occurs with one high‐flow year observed in 2017 (Figure 5), similar observations have been made in previous work on late‐fall‐run Chinook Salmon (Courter et al 2016; Perry et al 2018; Henderson et al 2019). Anomalous wet years like 2017 are important to consider because California remains in a state of extended drought, and obtaining data for years like this is likely to be difficult given their importance for fish survival.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, we observed that higher flow at the reach scale had a more positive effect on survival in dry years with low flow than it did in wet years with high flow. Although the interaction between annual flow and intra‐annual reach flow occurs with one high‐flow year observed in 2017 (Figure 5), similar observations have been made in previous work on late‐fall‐run Chinook Salmon (Courter et al 2016; Perry et al 2018; Henderson et al 2019). Anomalous wet years like 2017 are important to consider because California remains in a state of extended drought, and obtaining data for years like this is likely to be difficult given their importance for fish survival.…”
Section: Discussionsupporting
confidence: 87%
“…Interannual reach flow was calculated by standardizing flow to each reach’s mean flow:zinter,d,y,k=Qd,y,k-normalμkσk,whereas intra‐annual flow was calculated by standardizing daily flow within each reach and year:zintra,d,y,k=Qd,y,k-normalμy,kσy,k,where zinter,d,y,k and zintra,d,y,k are the inter‐ and intra‐annual reach flows on day d in year y and reach k ; Qd,y,k is discharge; μk and μy,k are the means of Qd,y,k for each reach and each reach and year, respectively; and σk and σy,k are the SDs of Qd,y,k for each reach and each reach and year. Including intra‐annual reach flow allowed us to examine whether large freshet events within a reach would increase survival relative to the mean flow for that year (Cavallo et al 2013; Courter et al 2016). We included intra‐annual reach flow in models with mean annual flow at Bend Bridge because scaling intra‐annual flow by both year and reach removes the effect of annual differences in intra‐annual reach flow, thus eliminating correlation between these variables.…”
Section: Methodsmentioning
confidence: 99%
“…It is likely that such pulse flows will engendered larger cohort‐wide survival gains than predicted here: Flow pulses are known to promote juvenile Chinook salmon to initiate their downstream migration (Sykes et al 2009), allowing a larger portion of the population to take advantage of the associated improvements in survival. Courter et al (2016) used managed flow releases in the Yakima River, Washington, to show the positive impact of increased flow on Chinook salmon smolt survival, which was then used to implement a minimum flow target. Experimental pulse flows may also help decouple the mechanisms driving increased survival, because increased flows through reservoir releases may not affect temperature and turbidity the same as storm‐related flow increases.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we more closely examine the underlying components of a flow–survival relationship that was quantified by Courter et al (in press; see also Courter et al ). This study found that survival of juvenile Chinook salmon ( Oncorhynchus tshawytscha ) was positively related to river discharge in the ‘Roza Reach’ of the Yakima River, Washington, USA, an 18‐km section of river downstream of a dam that diverts up to 80% of the river's flow.…”
Section: Introductionmentioning
confidence: 99%